Effects of pre-determined barbell hip thrusting surface height on motor unit recruitment and activation patterns - McCarty, A. R. (Liberty University, 2021)
Several variations of the barbell hip thrust that manipulate stance width and resistance type rather than surface height to better isolate muscle groups that act as prime movers for the exercise have been previously researched. The purpose of this study was to identify the effects of hip thrusting surface heights on neuromuscular activity in the gluteus maximus (GM), vastus lateralis (VL), and biceps femoris (BF). Twelve averagely fit, resistance trained individuals were recruited for this study. Participants completed a dynamic warm-up followed by 10 repetition max (RM) testing of the barbell hip thrust. Prior to trials, root mean square (RMS) values collected by surface electromyography (sEMG) during maximal voluntary isometric contractions of the (GM), (VL), and (BF) to enable data normalization. Three 10RM sets of the barbell hip thrust were performed on surface heights of 16.00 inches, 17.25 inches, and 18.50 inches. RMS values from each set were averaged across all 10 repetitions and statistical analysis was performed using a Friedman test with Wilcoxon post-hoc for significant differences. Kendall`s W was used to determine effect size. Results demonstrated no significant change in GM activity among all surface heights (x2(2)=1.167, W=0.049, p=0.558). A significant increase in activity of the VL was found with the Friedman test (x2(2)=8.000,W=0.333, p=0.018). With post-hoc analysis, the significant change only occurred from 16 inches to 18 inches (Z= -2.040, p=0.041). A significant decrease activity in the BF was also found with the Friedman test (x2(2)=10.5000, W=0.438; p=0.005), but the significant decrease was only found from 16 inches to 17 inches (Z= -2.353, p=0.019). Overall, no significant differences were found among bench heights for GM activation. However, as VL activation was found to increase as surface height increased, a higher bench height may be used to more efficiently recruit the VL during hip thrust. Conversely, as surface height decreased, the involvement of the BF increased. Study outcomes suggest that lower bench heights may be more efficient at recruiting the BF during the barbell hip thrust.